# Solve for z 7z+4(z-2)-z=5z-2(z-4(-z))

7z+4(z-2)-z=5z-2(z-4(-z))
Simplify 7z+4(z-2)-z.
Simplify each term.
Apply the distributive property.
7z+4z+4⋅-2-z=5z-2(z-4(-z))
Multiply 4 by -2.
7z+4z-8-z=5z-2(z-4(-z))
7z+4z-8-z=5z-2(z-4(-z))
11z-8-z=5z-2(z-4(-z))
Subtract z from 11z.
10z-8=5z-2(z-4(-z))
10z-8=5z-2(z-4(-z))
10z-8=5z-2(z-4(-z))
Simplify 5z-2(z-4(-z)).
Simplify each term.
Multiply -1 by -4.
10z-8=5z-2(z+4z)
10z-8=5z-2(5z)
Multiply 5 by -2.
10z-8=5z-10z
10z-8=5z-10z
Subtract 10z from 5z.
10z-8=-5z
10z-8=-5z
Move all terms containing z to the left side of the equation.
Add 5z to both sides of the equation.
10z-8+5z=0
15z-8=0
15z-8=0
Add 8 to both sides of the equation.
15z=8
Divide each term by 15 and simplify.
Divide each term in 15z=8 by 15.
15z15=815
Cancel the common factor of 15.
Cancel the common factor.
15z15=815
Divide z by 1.
z=815
z=815
z=815
The result can be shown in multiple forms.
Exact Form:
z=815
Decimal Form:
z=0.53‾
Solve for z 7z+4(z-2)-z=5z-2(z-4(-z))

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top